Students’ Perception on Learning Speaking English by Using English Domino Games: The Case of a Private University - Oktavia, Diana; Lestari, Renda (Indonesian Research Journal in Education |IRJE|, 2022)
This research aimed to see the students’ perception in practicing speaking English using the English Domino game. It was conducted using qualitative research with a case study approach. Fifteen students of the English Department at a private university in Muara Bungo were chosen by using purposive sampling. Furthermore, this research used interviews related to their experience and motivation in speaking English with the domino games to collect the data. The results indicated that the students’ motivation in practicing speaking in English increased by using the English domino games. Most of the students felt relaxed and confident to speak while playing English Domino. They were also excited and motivated to take their turns in telling the connected story. This kind of game can be an alternative for teaching English, particularly speaking in a non-English speaking country.